Expression of aquaporin 4 in the chicken ovary in relation to follicle development. (16th May 2017) - Nowak, M; Grzesiak, M; Saito, N; Kwaśniewska, M; Sechman, A; Hrabia, A
Contents: In the mammalian ovary, aquaporins (AQPs) are thought to be involved in the regulation of fluid transport within the follicular wall and antrum formation. Data concerning the AQPs in the avian ovary is very limited. Therefore, the present study was designed to examine whether the AQP4 is present in the chicken ovary, and if so, what is its distribution in the ovarian compartment of the laying hen. Localization of AQP4 in the ovarian follicles at different stage of development was also investigated. After decapitation of hens the stroma with primordial follicles and white (1–4 mm), yellowish (4–8 mm), small yellow and the three largest yellow pre‐ovulatory follicles F3‐F1 (F3 < F2 < F1; 20–36 mm) were isolated from the ovary. The granulosa and theca layers were separated from the pre‐ovulatory follicles. The AQP4 mRNA and protein were detected in all examined ovarian compartments by the real‐time PCR and Western blot analyses, respectively. The relative expression of AQP4 was depended on follicular size and the layer of follicular wall. It was the lowest in the granulosa layer of pre‐ovulatory follicles and the highest in the ovarian stroma as well as white and yellowish follicles. Along with approaching of the largest follicle to ovulation the gradual decrease in AQP4 protein level in the granulosa layer was observed. Immunoreactivity for AQP4 was present in the granulosa and theca cells (theca interna ≥ theca externa > granulosa). The obtained results suggest that AQP4 may take part in the regulation of water transport required for follicle development in the chicken ovary.